BEYOND ORGANIC OF MANAGEMENT CONTROL STRUCTURE - Hanif Hanif (Jurnal Akuntansi, 2022)
The research objective is to find a new management control structure, in addition to the existing models: mechanistic and organic. The approach used is hermeneutic to reinterpret the text of management control structure in the Padang restaurant from the relevant literature. After finding the meaning of the text, then field observations were carried out. All relevant literature is positioned as a neutral text which is then reinterpreted to get the essence of the concept of management control structure. The research finding is  the design of the Padang restaurant management control structure is the development of the organic model. Each restaurant branch is an autonomous organizational sub-unit, which includes three main characteristics, first, a horizontal and non-hierarchical organizational structure design, and a strategic business unit character. Managers in each branch are given full authority in making operational decisions of the company, a picture of radical decentralization can be seen. Second, the communication network follows the design rhythm of a flat organizational structure, namely fluid communication, dominated by informal communication. The third is budgeting, which is flexible, that is, there is no conventional budgeting that contains details, but only outlines.